Effect of berry maturity stages on the germination and protein constituents of African nightshade (Solanum scabrum) seeds - Noella Andenyi Ekhuya; Mary Abukutsa Onyango; Jennifer Senkler; Traud Winkelmann; Christin Bündig (Scientific Reports)
Abstract African nightshade (Solanum scabrum) is a vegetable of great importance in several African countries. Production by seed is constrained by limited access to high quality seed, leaving farmers unable to meet the growing demand. The aim of this study was to investigate effects of berry maturity stages (mature green and purple) on germination and protein components of African nightshade seeds. Nine accessions were used for the germination assays and three selected for the proteomics. The seeds harvested at the purple ripe stage showed a higher germination percentage than seeds harvested at the mature green stage. Seeds of three accessions, which showed different germination responses depending on maturity, were subjected to gel-based proteome comparison followed by mass spectrometry. Analysis revealed a total of 563 spots, of which 19–23% were differentially abundant between the two harvest times. This is the first study to utilise proteomics in African nightshade. Four types of seed storage proteins were identified. Identified proteins were associated with seed maturation, indicating more advanced maturation stages in accessions with higher germination capacity. In addition, a reference proteome map of S. scabrum was created using GelMap platform ( www.gelmap.de ). Colour change of African nightshade berries seems to be a suitable indicator for seed maturity.